Preoperative Serum Albumin, Serum Prealbumin, Serum Transferrin and Body Mass Index as Predictors of Postoperative Morbidity and Mortality in Laparotomy Cases: A Prospective Observational Study - Garlapati Sai Teja; S Biradar Dayanand; B Patil Mallikarjun; U Sindagikar Vikram; B Suntan Anand; Hanchinal Avinash (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Malnutrition significantly impacts postoperative outcomes in patients undergoing emergency laparotomy. Despite advances in surgical care, the role of preoperative nutritional parameters in predicting surgical outcomes remains crucial. Aim: To study the efficacy of preoperative serum albumin, serum prealbumin, serum transferrin and Body Mass Index (BMI) as predictors of postoperative morbidity and mortality in laparotomy cases. Materials and Methods: A prospective observational study was conducted at BM Patil College Hospital and Research Center, Vijayapura, Karnataka, India, from April 2023 to March 2024, which included 83 patients undergoing emergency laparotomy were included. Preoperative serum albumin, prealbumin, transferrin levels and BMI were measured. Primary outcomes included postoperative complications, mortality and length of hospital stay. Chi-square test, Student’s t-test, and Receiver Operating Characteristic curve (ROC) analysis were used for statistical evaluation (p<0.05). Results: The study population predominantly comprised middle-aged adults, with 34 (41%) aged 41-60 years, and showed a male predominance i.e., 58 (69.9%). Low albumin levels (<2.5 g/dL) were significantly associated with wound infection rates (77.8%, p<0.001). Transferrin levels <160 mcg/dL were associated with increased mortality (18.9%, p=0.04). Higher BMI was associated with increased mortality (p=0.007). ROC curve analysis showed BMI as the strongest predictor of mortality (AUC=0.735). Wound infection occurred in 48.2% of cases, with overall mortality rate of 9.6%. Conclusion: Preoperative serum albumin, prealbumin, transferrin, and BMI are significant predictors of postoperative outcomes in laparotomy patients, with low protein levels linked to complications and BMI showing the strongest association with mortality. Routine nutritional assessment is essential for improving surgical outcomes.